Application of BOLD Magnetic Resonance Imaging for Evaluating Regional Volumetric Foot Tissue Oxygenation: A Feasibility Study in Healthy Volunteers. Issue 5 (May 2016) - Stacy, M.R.; Qiu, M.; Papademetris, X.; Caracciolo, C.M.; Constable, R.T.; Sinusas, A.J.
Abstract : Objective/Background: To evaluate the feasibility and repeatability of applying blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI) in the feet to quantify regional dynamic changes in tissue oxygenation during proximal cuff occlusion and reactive hyperemia. Methods: Ten healthy male subjects underwent BOLD and T1-weighted imaging of the feet on two separate occasions, using a 3-T scanner. Dynamic changes in BOLD signal intensity were assessed before and during proximal cuff occlusion of the thigh and during reactive hyperemia, and BOLD time course data were evaluated for the time-to-half ischemic minimum, minimum ischemic value, peak hyperemic value, time-to-peak hyperemia, time-to-half peak hyperemia, and end value. T1-weighted images were used for segmentation of volumes of interest (VOI) in anatomical regions of the foot (heel, toes, dorsal foot, medial and lateral plantar foot). Repeatability of vascular responses was assessed for each foot VOI using semiautomated image registration and quantification of serial BOLD images. Results: The heel VOI demonstrated a significantly higher peak hyperemic response, expressed as percent change from baseline BOLD signal intensity, compared with all other VOIs of the foot (heel, 7.4 ± 1.2%; toes, 5.6 ± 0.8%; dorsal foot, 5.7 ± 1.6%; medial plantar, 5.6 ± 1.7%; lateral plantar, 5.6 ± 1.5% [ p < .05]). Additionally, the lateral plantar VOI had a significantly lower terminal signal intensity value (i.e., end value) when compared with all foot VOIs ( p < .05). BOLD MRI was repeatable between visits in all foot VOIs, with no significant differences between study visits for any of the evaluated functional indices. Conclusion: BOLD MRI offers a repeatable technique for volumetric assessment of regional foot tissue oxygenation. Future application of BOLD imaging in the feet of patients with peripheral vascular disease may permit serial evaluation of regional tissue oxygenation and allow for improved assessment of therapeutic interventions targeting specific sites of the foot.